2022
DOI: 10.3390/cancers14040879
|View full text |Cite
|
Sign up to set email alerts
|

What Does PET Imaging Bring to Neuro-Oncology in 2022? A Review

Abstract: PET imaging is being increasingly used to supplement MRI in the clinical management of brain tumors. The main radiotracers implemented in clinical practice include [18F]FDG, radiolabeled amino acids ([11C]MET, [18F]FDOPA, [18F]FET) and [68Ga]Ga-DOTA-SSTR, targeting glucose metabolism, L-amino-acid transport and somatostatin receptors expression, respectively. This review aims at addressing the current place and perspectives of brain PET imaging for patients who suffer from primary or secondary brain tumors, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 102 publications
(129 reference statements)
1
13
0
Order By: Relevance
“…Although multiparametric MRI represents the current imaging gold standard in primary and metastatic brain neoplasms, PET studies have the unique and complementary ability to evaluate and characterize the metabolic patterns within the tumor and non-tumor tissues through the use of selected radiolabeled tracers [ 84 , 85 , 86 ]. The roles of different PET tracers in tumor diagnosis and post-treatment response assessment have been largely discussed and validated by international consensuses and recommendations [ 87 , 88 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although multiparametric MRI represents the current imaging gold standard in primary and metastatic brain neoplasms, PET studies have the unique and complementary ability to evaluate and characterize the metabolic patterns within the tumor and non-tumor tissues through the use of selected radiolabeled tracers [ 84 , 85 , 86 ]. The roles of different PET tracers in tumor diagnosis and post-treatment response assessment have been largely discussed and validated by international consensuses and recommendations [ 87 , 88 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tripathi et al revealed in a recent comparative study that 11 C-MET should be the radiotracer of choice in the evaluation of recurrence of primary brain tumors, since 11 C-MET has a better sensitivity for detection and delineation of the possible recurrent tumor, as well as secondary deposits . The advantage of amino acid PET tracers over FDG is that they do not build up excessively in the healthy brain . PET imaging with 11 C-MET could not become a routine investigation due to the very short half-life of 11 C (20 min), and it is limited to those centers with an in-house cyclotron and the requisite synthesis equipment.…”
Section: Radiotracers and Tomographic Modalities In Nuclear Medicinementioning
confidence: 99%
“…Nonetheless, there has been an expanding role of PET-CT in neuro oncology. In addition to FDG, several radiopharmaceuticals have been developed and used to assess important biologic and physiologic properties of brain tumors including metabolism, proliferation, blood flow/perfusion, hypoxia, amino acid uptake, somatostatin-receptor expression [ 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. Expanded neuro oncologic applications for a variety of radiopharmaceuticals, including those FDA-approved for other indications, is well supported in the literature.…”
Section: Neuro Oncologymentioning
confidence: 99%
“…Although FDG PET-CT is being used effectively for treatment planning in head and neck tumors, it has not been shown to be of benefit in helping to define treatment volume in gliomas [ 115 , 116 ]. There are several PET radiopharmaceuticals that are not, at this point, FDA approved, but which show superiority in characterizing lesions in neuro oncology, including 11 C-MET, 18 F-DOPA, 18 F-FET [ 105 , 117 ]. Although future clinical PET imaging may be expanded globally to incorporate these or similar radiopharmaceuticals for neuro oncology, the current FDA approved agent for PET brain imaging in the US is FDG.…”
Section: Neuro Oncologymentioning
confidence: 99%